Consumption of fruits, vegetables, and risk of hematological malignancies: a systematic review and meta-analysis of prospective studies. Issue 2 (1st February 2018) - Sergentanis, Theodoros N.; Psaltopoulou, Theodora; Ntanasis-Stathopoulos, Ioannis; Liaskas, Athanasios; Tzanninis, Ioannis-Georgios; Dimopoulos, Meletios-Athanasios
Abstract: We examined the association between fruit/vegetable consumption and the risk of hematological malignancies in cohort studies (end of search: August 31, 2016). Total fruit consumption was not associated with the risk of non-Hodgkin lymphoma (NHL) (RR = 1.03, 95% CI: 0.92–1.16, I 2  = 12.1%, n  = 7), acute myeloid leukemia (RR = 1.23, 95% CI: 0.94–1.61, I 2  = 0%, n  = 3), multiple myeloma (MM; RR = 1.05, 95% CI: 0.72–1.55, I 2  = 60.0%, n  = 4), and Hodgkin lymphoma. However, citrus fruit consumption was associated with reduced NHL risk (RR = 0.85, 95% CI: 0.73–1.00, p  = .044, I 2  = 0%, n  = 6). Vegetable intake was marginally associated with reduced NHL risk (RR = 0.89, 95% CI: 0.79–1.00, p  = .056, I 2  = 16.2%, n  = 7), but not with acute myeloid leukemia, multiple myeloma, and Hodgkin lymphoma risk. Nevertheless, NHL risk was inversely associated with cruciferous vegetable consumption (RR = 0.84, 95% CI: 0.71–1.00, p  = .047, I 2  = 0%, n  = 3). Notably, combined fruit/vegetable consumption was associated with decreased NHL risk (RR = 0.79, 95% CI: 0.65–0.96, I 2  = 11.2%, n  = 3). This meta-analysis reveals possible protective effects; however, confounding and reporting bias could have affected the results.